The Response of Balinese Society on 2019 Indonesian Simultaneous Elections - Bandiyah, Bandiyah; Ginting, Richard Togaranta (Jurnal Politik Indonesia: Indonesian Political Science Review, 2020)
This research aimed to determine the response of Balinese Society on 2019 Indonesian Simultaneous Elections. The response includes three components, namely perception, participation, and attitude. This research used a descriptive type with a quantitative approach. This study was conducted in Bali Province, especially 9 (nine) districts and cities that held simultaneous elections on April 17, 2019. Based on data compiled from General Election Commission (KPU), Bali Province had 716 villages with 12,384 polling stations (TPS). Based on  Bali’s DPT 2019 from General Election Commission (KPU), there were 3,130,288 voters. The number of samples was determined using the Slovin’s formula with a 5% significance level that obtained 400 respondents. This study used a cluster sampling technique. Based on the analysis of the data obtained, the responses of the Balinese society on the implementation of the 2019 simultaneous elections were fair and good. The perception of the Balinese society on the implementation of the 2019 simultaneous election was good with an average score of 4.04 (out of 5.00). The participation of the Balinese society on the holding of the 2019 simultaneous elections was fairly good with an average score of 3.62 (out of 5.00). The attitude of the Balinese society on the implementation of 2019 simultaneous elections was good with an average score of 4.26 (out of 5.00). This is an interesting finding, considering that Bali is an area known for representing the Partai Demokrasi Indonesia-Perjuangan (PDIP), that naturally support for them through high political participation.